Laboratory comparison of vegetation and gravel on parameters affecting urban floods under different rainfall and runoff conditions - Hamidreza Ghazvinian; Hojat Karami (Journal of Water and Climate Change, 2023)
This research seeks to analyze and compare the performance of impervious surface as control (O), sandy loam substrate, gravel, gravel with geocell layer (GGE), rosemary (R), rosemary with geocell layer (RGE), turf (T), and turf with geocell layer (TGE) in the reduction of rainfall-runoff volume, time to start runoff (TSR), runoff coefficient (C), time to end runoff (TER), peak flow (PF) rate, time to peak (TP), and time base (TB) under three conditions of rainfall, horizontal runoff, and the combination of rainfall and runoff in a slope of 5% using a rainfall simulator. Regarding the factorial results of the effective parameters of the test mode and the test sample on TSR, TER, TP, TB, C, and PF, there was a significant difference at the 5% level between the data in all cases. In all cases, GGE treatment performed better compared to the rest of the test groups in reducing runoff and cumulative volume. On the other hand, treatments O and GGE experienced the highest and lowest flow rate, respectively. For a given test condition, the value of C is the lowest for the GGE treatment. HIGHLIGHTS The simultaneous laboratory investigation of rainfall and horizontal runoff can be effective in estimating the parameters affecting the flood.; Implementation of geocell to cover gravel, rosemary, and turf can be effective in reducing floods.; GGE had the best performance in reducing floods and improving parameters affecting it.;